Lynniagrapsolytica n. gen, n. sp. (Ciliophora: Apostomatida: Colliniidae), a Deadly Blood Parasite of Crabs with a Novel Pseudocytopharynx. (31st March 2021) - Metz, Daniel C.G.; Hechinger, Ryan F.
Abstract: We describe a new genus and species of blood‐dwelling apostome ciliate, Lynnia grapsolytica n. gen., n. sp. (Apostomatida: Colliniidae). A distinct kinety "hook" pattern on the tomite's posterior ventral face, coupled with its marine habitat and use of a decapod host, readily distinguishes this ciliate from all known colliniids. We detected the parasite in 12% of Pachygrapsus crassipes (Brachyura: Grapsidae) crabs in a California estuary and confirmed its presence at a Baja California rocky intertidal site. As existing methods failed to adequately stain this ciliate, we developed a new miniaturized silver carbonate impregnation staining method that produced excellent somatic and nuclear stains in all five observed cell types. A possibly unique trait is the active invagination of the tropho‐tomont's anterior to form a temporary "pseudocytopharynx, " likely used for feeding. Histological examination revealed that the ciliate invaded and damaged skeletal muscle, the heart, connective tissues, and gonads. Survivorship analysis indicated that infected crabs experienced 2.6 times greater daily mortality than uninfected crabs. Laboratory and field experimental infection attempts failed, suggesting a complex life cycle with outside‐host development. Phylogenetic analysis at the 18S and COI loci confirmed the ciliate's placement in the Colliniidae. We emend the diagnosis of Family Colliniidae.